Aspidistra micrantha (Asparagaceae, Nolinoideae), a new species from Vietnam with unusually small flowers - Vislobokov, Nikolay A.; Nuraliev, Maxim S.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P. (Phytotaxa, 2019)
Aspidistra micrantha is described and illustrated as a new species from southern Vietnam (Quang Nam province, Song Thanh Nature Reserve). The new species has globoid flowers, which are the smallest within the genus Aspidistra. In floral structure, the closest species to A. micrantha is A. urceolata, which is endemic to the Guizhou province of China, but strongly differs from the latter in some morphological features of the rhizome, leaves and position of anthers.